ISSUES OF ELIMINATING TAX AVOIDANCE OPPORTUNITIES DUE TO THE USE OF ONLINE TILLS AND VIRTUAL CASH REGISTERS IN THE DIGITAL ECONOMY - Sadullaev Rasulbek Palvanbaevich (Bright Mind Publishing, 2025)
The article analyzes the opportunities for tax evasion in the digital economy of the Republic of Uzbekistan, online trade, electronic services, electronic transactions and gives relevant proposals and recommendations.
Keywords: Tax authorities, taxpayer, business entity, hidden economy, digital economy, online till, virtual cash register, online commerce, e-services, electronic transactions.